Key enterprise architecture value drivers: results of a Delphi Study - Rodrigues, Luis Silva (2013)
The value of Enterprise Architectures is undoubtedly an issue that is of particular importance in organizations. In the current context of strong economic constraints and the need to justify the usefulness and investments on Enterprise Architectures are increasingly demanding an assessment and demonstration of its value. However, it is recognized that assessing and demonstrating the value of Enterprise Architecture is not an easy task. In our view, the lack of a clear understanding on what is important for Enterprise Architecture value assessment, the intangible nature of some benefits and the need to quickly demonstrate the Enterprise Architecture value are some of the main reasons for this difficulty. This article presents the results of an international Delphi study involving 63 experts which main objective was to identify, systemize and prioritize the key value drivers of the Enterprise Architecture.